DISCRIMINATION INDEX OF TEST ITEM IN ENGLISH MID YEAR TESTOF FOURTH GRADERS OF SEKOLAH KEBANGSAAN BANDAR SUNGAI BUAYAIN THE SCHOOL YEAR 2017 - Yoan Natalia Matahelumual; Dwi Winarsih; Lilia Indriani (Faculty of Education and Teachers Training, 2018)
In teaching English, teachers use the test to evaluate or assess the students progress and understanding. In this case, sometimes the teacher writes the English test items beyond the students’ ability and understanding. That is why students get confused with the test items. Therefore, the writer is interested in analyzing the discrimination index of the English mid year test items at SekolahKebangsaan Bandar Sungai Buaya, Selangor Malaysia in order to know the test given by the teacher. The objective of this research is to describe the discrimination index of English mid year test for the fourth graders of SekolahKebangsaan Bandar Sungai Buaya, Selangor Malaysia. The subject of this research is the English mid year test of the fourth graders of Utarid Class in Sekolah Kebangsaan Bandar Sungai Buaya, Selangor Malaysia in the school year 2017 and consist of 24 students. In conducting this research, the writer took the questions sheet and the students’ answer sheet of English mid year test for the fourth graders of Sekolah Kebangsaan Bandar Sungai Buaya in the school year 2017. According to data analysis, the writer summed up the conclusions as follows. Based on Naga’s Discrimination Index Parameter (1992) there are four test items are rejected because the discrimination index score is 0.00. It means that those four test cannot disriminate the students who who have already mastered the material and those who have not.